2018
DOI: 10.1002/hbm.24416
|View full text |Cite
|
Sign up to set email alerts
|

Specialized neural dynamics for verbal and tonal memory: fMRI evidence in congenital amusia

Abstract: Behavioral and neuropsychological studies have suggested that tonal and verbal short‐term memory are supported by specialized neural networks. To date however, neuroimaging investigations have failed to confirm this hypothesis. In this study, we investigated the hypothesis of distinct neural resources for tonal and verbal memory by comparing typical nonmusician listeners to individuals with congenital amusia, who exhibit pitch memory impairments with preserved verbal memory. During fMRI, amusics and matched co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
57
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 73 publications
16
57
2
Order By: Relevance
“…The fact that we observed delta-band entrainment in IFG with the task (Fig. 2B-C) is compatible with this region being a downstream node of the ventral auditory pathway (Zatorre et al, 1992;Gaab et al, 2003, Albouy et al, 2013, 2019. Expressions of beta-band activity during pitch processing have been previously reported in auditory regions (Cirelli et al, 2014;Fujioka et al, 2012), including during the pre-target time period (Florin et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fact that we observed delta-band entrainment in IFG with the task (Fig. 2B-C) is compatible with this region being a downstream node of the ventral auditory pathway (Zatorre et al, 1992;Gaab et al, 2003, Albouy et al, 2013, 2019. Expressions of beta-band activity during pitch processing have been previously reported in auditory regions (Cirelli et al, 2014;Fujioka et al, 2012), including during the pre-target time period (Florin et al, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…This functional gap between non-conscious and conscious pitch change detection in the amusic brain is currently attributed to altered brain connectivity between the superior temporal gyrus (STG) and the inferior frontal gyrus (IFG; Peretz, 2016). Dynamical causal modelling in MEG showed that amusic participants express both decreased backward connectivity between the right IFG and the right auditory cortex during pitch encoding (Albouy et al, 2013;Albouy et al, 2019) and decreased forward connectivity during pitch change detection (interpreted as reduced prediction error signalling; Albouy et al, 2015). In typical listeners, the role of fronto-temporal network connectivity in pitch change detection has been further documented using measures of oscillatory brain dynamics related to sensory input prediction and the relationship between rhythmic responses and entrained oscillations (Phillipes et al 2015, Tse et al 2018, Haegens & Zion Golumbic, 2018Nobre & van Ede, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The greater engagement of brain structures particularly involved in auditory cognition and predictive coding while listening to pleasant music, such as the right STG and the right IFG, further reinforces the idea that learning is crucial for the experience of musical pleasure. The right STG has been consistently implicated in various processes relevant for music perception, including pitch representation (Coffey et al, 2016;Johnsrude et al, 2000), tonal pattern processing (Foster and Zatorre, 2010a;Patterson et al, 2002), tonal working memory (Albouy et al, 2019), tonal learning (Herholz et al, 2016), and musical imagery (Herholz et al, 2012). Recent findings indicate that this right hemisphere specialization in music may arise from differential sensitivity to acoustical cues between the left and the right auditory cortices, with a specific sensitivity to spectral information in the right hemisphere and greater sensitivity to temporal information in the left (Albouy et al, 2020).…”
Section: Auditory Cortical Regionsmentioning
confidence: 99%
“…Indeed, only one previous functional neuroimaging study has examined the neural processing of spoken material in people with amusia. In this study no group differences were detected in task-related activation or functional connectivity during processing of speech (whereas group differences were observed during processing of tones; Albouy et al, 2018). However, this study used tasks for which pitch processing would not have been necessary (verbal memory), as well as a priori regions of interest derived from studies that used tonal/melodic (rather than linguistic) stimuli.…”
Section: [H1] Introductionmentioning
confidence: 74%
“…However, this finding can be explained by the pitch memory account, as the suprasegmental task requires detection of and memory for pitch patterns within a complex sequence, while the segmental task does not. Furthermore, an account of amusia which suggests that the disorder primarily stems from differences in structural connectivity cannot account for the recent finding that functional connectivity patterns do not differ between amusics and controls during a verbal memory task (Albouy et al 2018). We suggest, therefore, that amusics neglect pitch because they have implicitly learned that their memory for pitch is unreliable, and that this down-weighting of pitch is reflected in decreased functional connectivity between right auditory areas and downstream task-relevant areas which integrate information from perceptual regions.…”
Section: [H1] Discussionmentioning
confidence: 95%